Influencer-Driven Product Promotions on Social Media: Analyzing Youth Consumer Perceptions Through Functional Attitude Theory - Sriya, Ramakrishnan Teja; Deepak, Leah Mani (Journal of Global Economy, Business and Finance, 2025)
This study examines the effects of influencer-driven product promotions on social media and their impact on the perceptions of youth consumers. Grounded in the Functional Attitude Theory, it investigates how various functional attitudes are associated with consumer attitudes towards influencer marketing strategies. The research encompasses a diverse demographic range in terms of age, gender, education, and employment status. Employing a mixed-methods approach, quantitative data was collected through a structured survey distributed among social media users aged between 18 and 30, while qualitative insights were gathered through focus group discussions. The dataset's reliability was confirmed by reliability analysis, ensuring the robustness of the conclusions drawn. Factor analysis was employed to assess the suitability of the data for the study's constructs. The results indicate that functional attitudes, including entertainment, knowledge-seeking, social connection, and utilitarian needs, are positively correlated with consumer attitudes towards influencer-led promotions. These findings suggest that consumers perceive influencer-promoted products not only as desirable commodities but also as vehicles catering to their functional and psychological needs. The study further reveals that these associations vary across demographics, shedding light on the nuanced nature of influencer effectiveness. In conclusion, this research highlights the importance of aligning influencer marketing content with the functional motives driving consumer behavior. By recognizing the diversity of functional attitudes and their appeal to different consumer segments, both brands and influencers can tailor their strategies effectively. This study contributes to the evolving comprehension of influencer marketing by emphasizing the role of functional attitudes in shaping consumer perceptions and fostering favorable attitudes towards products promoted on social media.